Relationship between Organic Matter and Productivity of the Bakuok Lake Aur Sati Village, Tambang District, Kampar Regency, Riau Province - Natasya Margareth Pasaribu; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Several activities in the Bakuok Lake contribute the input of organic and inorganic matters to the waters, and thus increase the concentration of nitrate and phosphate in the water. A research aims to understand the relationship between organic matter and nutrients (Nitrate and Phosphate) in the Bakuok Lake has been carried out in June-July 2019. There were three stations namely station 1 (around the plantation area), station 2 (in the middle of the lake) and station 3 (around the net cage area). Each station has 2 sampling points namely the surface and 2 Secchi depth. Sampling was done 3 times, once/week. Water quality parameters measured were biochemical oxygen demand, dissolved oxygen, free carbon dioxide, nitrate, phosphate, temperature, transparency, pH, and ammonia. The water quality value were as follows: biochemical oxygen demand 4.80-6.32 mg/L, dissolved oxygen 6.57-7.54 mg/L, carbon dioxide 9.37-13.86 mg/L, nitrate 0.0207-0.0319 mg/L, phosphate 0.0385-0.0553 mg/L, temperature 29.3-31.3oC, transparency 58-87 cm, pH 5, and ammonia 0.0132-0.0165 mg/L. The relationship between organic matter with nitrate and phospate was 0.96 or very strong.Keywords: Oxbow Lake, Nutrients, Water Quality